Food groups and weight gain in Japanese men. Issue 3 (11th April 2014) - Ibe, Y.; Takahashi, Y.; Sone, H.
Summary Identifying subjects at high risk of weight gain according to consumption of food groups is important for individualizing nutritional education, but prospective studies of this issue have been few. We determined whether intake of specific food groups could predict future weight gain. We evaluated data from health checkups on 1236 Japanese men aged 28 to 87 years in 2005 and 2006. Dietary intake was assessed by a 24‐h dietary recall at baseline. Weight change was measured after 1 year. Weight increased in 44.7% (n = 553) of participants. Multivariate regression analysis involving many food groups showed a significant association between sugar intake and weight gain after adjustment for age, body mass index (BMI), total energy intake, alcohol, smoking and regular physical exercise (β = 0.22, P = 0.04). The effect of intake of 'fats and oils' was significant when adjusted for age and BMI, however, it became insignificant after adjustment for age, BMI and total energy intake. Intake of sugar, which was evaluated as a food group, was predictive of subsequent weight gain among Japanese men, even after adjustment for many confounders. This corroborates the evidence so far concerning the links between sugar intake and weight gain. Further long‐term research is required to give robust recommendation to the public.